"Saluting" perceived sense of coherence in people with dementia by nurses. Issue 3 (21st September 2015) - Lillekroken, Daniela; Hauge, Solveig; Slettebø, Åshild
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Nurses employed in nursing homes have a unique insight into the lives of people with dementia (PwD) and into the factors that may support and possibly enhance their sense of coherence (SOC). It is currently not known precisely which factors contribute to supporting the SOC in PwD; therefore, in order to address the paucity of research in this area, the purpose of this paper is to identify and present these factors as they were perceived by nurses. Design/methodology/approach – The study employed a qualitative explorative design. Participant observation and focus group interviews were the data collection methods. The participants were nurses employed in special dementia units from two Norwegian nursing homes. Data were analysed using qualitative content analysis. Findings – Data analysis highlighted a main category, with additional three generic categories. The main category, "creating order out of chaos" concerns the nurses' explanations about how they could create order in the lives of PwD lives. This main category is subdivided into three generic categories; "establishing continuity", "ensuring predictability" and "building confidence". These categories were assessed as "salutary" factors that may contribute to supporting the SOC in PwD. Originality/value – This paper highlights the importance of continuity, predictability and confidence as factors that may contribute to counterbalancing the state of chaos and to supporting the SOC in PwD. The findings add a salutogenic perspective to dementia care and research.